Histaminergic Receptors Modulate Spinal Cord Injury-Induced Neuronal Nitric Oxide Synthase Upregulation and Cord Pathology: New Roles of Nanowired Drug Delivery for Neuroprotection - Sharma H.S.; Patnaik R.; Muresanu D.F.; Lafuente J.V.; Ozkizilcik A.; Tian Z.R.; Nozari A.; Sharma A. (My University, 2025)
The possibility that histamine influences the spinal cord pathophysiology following trauma through specific receptor-mediated upregulation of neuronal nitric oxide synthase (nNOS) was examined in a rat model. A focal spinal cord injury (SCI) was inflicted by a longitudinal incision into the right dorsal horn of the T10–11 segments. The animals were allowed to survive 5 h. The SCI significantly induced breakdown of the blood–spinal cord barrier to protein tracers, reduced the spinal cord blood flow at 5 h, and increased the edema formation and massive upregulation of nNOS expression. Pretreatment with histamine H1 receptor antagonist mepyramine (1 mg, 5 mg, and 10 mg/kg, i.p., 30 min before injury) failed to attenuate nNOS expression and spinal cord pathology following SCI. On the other hand, blockade of histamine H2 receptors with cimetidine or ranitidine (1 mg, 5 mg, or 10 mg/kg) significantly reduced these early pathophysiological events and attenuated nNOS expression in a dose-dependent manner. Interestingly, TiO2-naowire delivery of cimetidine or ranitidine (5 mg doses) exerted superior neuroprotective effects on SCI-induced nNOS expression and cord pathology. It appears that effects of ranitidine were far superior than cimetidine at identical doses in SCI. On the other hand, pretreatment with histamine H3 receptor agonist α-methylhistamine (1 mg, 2 mg, or 5 mg/kg, i.p.) that inhibits histamine synthesis and release in the central nervous system thwarted the spinal cord pathophysiology and nNOS expression when used in lower doses. Interestingly, histamine H3 receptor antagonist thioperamide (1 mg, 2 mg, or 5 mg/kg, i.p.) exacerbated nNOS expression and cord pathology after SCI. These novel observations suggest that blockade of histamine H2 receptors or stimulation of histamine H3 receptors attenuates nNOS expression and induces neuroprotection in SCI. Taken together, our results are the first to demonstrate that histamine-induced pathophysiology of SCI is mediated via nNOS expression involving specific histamine receptors. © 2017 Elsevier Inc.